Seasonal high-resolution sensor data for pCO2, pCH4 and water quality in south coast of Finland, northern Baltic Sea - Asmala, Eero; Scheinin, Matias (PANGAEA, 2022)
Flow-through pCO2, pCH4, air pressure, fDOM, turbidity, chlorophyll a, temperature and salinity measurements in the coastal waters of SW Finland (northern Baltic Sea) and several adjacent rivers and creeks over nearly two ice-free seasons; 2020 (20.04. - 13.10.) and 2021 (19.04. - 06.08.) Surface water flow-through system aboard a rigid inflatable boat (see Scheinin & Asmala, 2020). All the measured variables are combined into a single data set, because, the same water was passed through all the sensors virtually simultaneously (within less than 3 seconds). The data for pCO2 and pCH4 include some short gaps due to automatic re-zeroing. Depth of water intake: 50 cm. Flow rate: 29.0 L/min for the whole flow-through system and reduced to 2.4 L/min for the GHG sensors. Travelling speed: 0 m/s – 12 m/s. Logging interval: 5 seconds (0 m – 60 m). Hydraulic lag: ~ 8 seconds. Geospatial referencing for all the data has been corrected for the hydraulic lag and the sensor specific response times (see Scheinin & Asmala, 2020).
Keywords: Baltic Sea; CH4; chlorophyll fluorescence; CO2; FDOM; organic matter cycling; Salinity; turbidity